Characteristics Overview Mother with Incidence of Low Birth Weight Babies at dr. Hospital H. L. M Baharudin, M. Kes in 2023 - Indra Farah Ni'sa; Wa Ode Ikrawati; Wa Ode Siti Fidia Husuni (International Journal of Health and Social Behavior, 2024)
Introduction: Low birth weight babies are babies whose birth weight is <2500 grams, which is caused by maternal, nutritional, age, parity and economic factors. Objective:To determine the characteristics of mothers with LBW incidents at RSUD dr. HLM Baharuddin, M.Kes 2023. Method: This research was quantitative descriptive, conducted at RSUD dr.Baharuddin, M.Kes on mothers who gave birth to low birth weight babies for the period January - June 2023 with a sample of 30 mothers determined by total sampling. Results: LBW occurred in mothers aged 20-35 years, namely 23 people (76.67%), mothers with multiparous parity, namely 18 mothers (60%), mothers with a birth interval of ≥2 years, namely 25 mothers (56.67%) , 18 mothers (60%) suffered from the disease, and the highest incidence of LBW was in mothers with ≥high school education as many as 19 mothers (63.33%).Conclusion: Mothers with LBW incidence at the age of 20-35 years were 23 mothers (76.67%), Age <20/>35 years 7 mothers (23.33%), Primiparous parity 8 mothers (26.67), Multiparous 18 mothers (60%), Grandemultiparous 4 mothers (13.33%), Birth interval <2 years 5(16.67%), ≥2 years 25(56.67%), 18 mothers with disease (60%) 12 mothers (40%) did not suffer, had ≤junior high school education 11(36.67%) and ≥high school education 19(63.33% )